Isolation and Identification of the Types of Bacteria that Cause Irritable Bowel Syndrome - Noor Mahmood Sultan; Abeer Abbas Ali; Hayder Jaleel Mardan (Medical Journal of Babylon)
Background: Irritable bowel syndrome (IBS) is a chronic functional gastrointestinal (GI) disorder with an estimated prevalence of 10% around the globe. Human body possesses about 39 trillion of microbial cells, the majority of which inhabit the GI tract. The recent realization is that small intestinal bacterial overgrowth may be associated with symptoms of IBS. Aim: The current work aimed at the isolation and identification of different bacteria strains from IBS patients. Materials and Methods: One hundred and thirty patients of different sex and ages were diagnosed with IBS (which was previously diagnosed by a specialist doctor) in the time period from November 2021 to May 2022. Results: The current results showed that there is a correlation between the number and percentage of isolates for each type of bacteria with a group of study factors, where in terms of sex, females were more. Concerning the age group, the most common age group was 36–55 years. On the other hand, the percentage of uneducated people was higher in the current study. It also showed the other factor, which is the possession of domestic animals; the majority of the study population was not owning animals. Regarding the prevalent weight, the body mass index (BMI) of 24–29.9 is the highest. The percentage of nonsmokers was also the highest, and the highest percentage of isolates was for Escherichia coli in all. Conclusions: This study proved that E. coli is the most common type of bacteria that has an effect on IBS patients and that Helicobacter pylori has the least effect.